Environmental efficiency of pork supply chains originating from Punjab - Kaur, Simran; Singh, Jasdev (Agricultural Economics Research Review, 2025)
The present study has been conducted to analyse the marketing efficiency in relation to the environmental efficiency of pork supply chains originating from Punjab. Two distinct markets - local and distant (North-Eastern India) were identified during the study. Results revealed an inverse relationship between the length of pork supply chain and marketing efficiency. Further, a direct relationship was found between marketing efficiency and environmental efficiency. Amount of CO2 released during the delivery of one kilogram of pork in the distant market was nearly double (35-37 kg) in comparison to that released in the local supply chains (15-20 kg). Thus, it is suggested that short supply chains of pork should be promoted.